PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA SERAB COFFEE BREWERY DI DEPOK JAWA BARAT - Alifia Salsabela Putri, Nanda; Haryantini (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the variables of product quality (X1), and promotion (X2), purchasing decisions (Y), and the influence of product quality and promotion on purchasing decisions at Serab Coffee Brewery in Depok, West Java. This research method uses quantitative methods. The population in this research was 88,000 consumers, then the sample taken in this research was 100 respondents. In this research, the technique used is Non-Probability Sampling. The results of the Product Quality variable have a significant effect on Purchasing Decisions with a calculated t value of 3.448 > t table 1.660 and a sig value. < 0.1 (0.001 < 0.1). The results of the Promotion variable have a significant effect on Purchasing Decisions with a calculated t value of 4.041 > t table 1.660 and a sig value. < 0.1 (0.000 < 0.1). The results of the Product Quality and Promotion variables simultaneously have a significant effect on Purchasing Decisions with a calculated f value of 11.421 > f table 2.36 and a sig value. < 0.1 (0.000 < 0.1).